2015
DOI: 10.1186/s40643-015-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface physicochemical properties of selected single and mixed cultures of microalgae and cyanobacteria and their relationship with sedimentation kinetics

Abstract: Background: Microalgae are photosynthetic microorganisms presenting a diversity of biotechnological applications. However, microalgal cultivation systems are not energetically and economically feasible. Possible strategies that can be applied to improve the feasibility of microalgal production include biofouling control in photobioreactors, the use of attached growth systems and bioflocculation. These processes are ruled by surface physicochemical properties. Accordingly, the surface physicochemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…Higher values determined for γ s - indicate that the studied microalgae showed a strong electron-donating property. It should be stated that similar results were obtained in previous studies by Ozkan and Berberoglu (2013) and Gonçalves et al (2015) [ 3 , 29 ]. In addition, γ s + values close to zero are in accordance with the Oss et al (2008) model, which predicts almost the non-existence of electron acceptor parameters [ 3 ].…”
Section: Resultssupporting
confidence: 91%
“…Higher values determined for γ s - indicate that the studied microalgae showed a strong electron-donating property. It should be stated that similar results were obtained in previous studies by Ozkan and Berberoglu (2013) and Gonçalves et al (2015) [ 3 , 29 ]. In addition, γ s + values close to zero are in accordance with the Oss et al (2008) model, which predicts almost the non-existence of electron acceptor parameters [ 3 ].…”
Section: Resultssupporting
confidence: 91%
“…However, it should be noted that, in some applications, the surface characteristics of the abiotic substrata could be affected by the roughness, heterogeneity, and adsorption of molecules. ,, However, the surface characteristics of the cell could be affected by the extracellular polymeric substances pili and flagella , and might change in response to the changes in the culture conditions and different stages of cell cultivation . In some applications, mixed cultivation might exist, thus, the species interactions might also significantly influence the cell adhesion . Although these differences might affect the accuracy of the criterion, the study demonstrated that the criterion was still valuable for the prediction of adhesion in the majority of cases.…”
Section: Resultsmentioning
confidence: 91%
“…44 In some applications, mixed cultivation might exist, thus, the species interactions might also significantly influence the cell adhesion. 49 Although these differences might affect the accuracy of the criterion, the study demonstrated that the criterion was still valuable for the prediction of adhesion in the majority of cases. Follow-up studies would be conducted to amend the criterion for better applicability.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The discrepancy may contribute to the differential occurrence of Microcystis blooms in different seasons. Notably, during the logarithmic phase, the contact angles of Microcystis with solvent were smaller than that of M. aeruginosa LEGE 91344 (less than 90°; Gonçalves et al, 2015 ), and A. variabilis (greater than 90°; Volpe and Siboni, 1997 ; Ozkan and Berberoglu, 2013 ; Hao et al, 2017 ). Compared with other freshwater cyanobacteria, S. salina LEGE 06079, Synechocystis sp., and A. variabilis are all hydrophobic ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%